Analysis Function And Meaning Affix In Lyrics Song Fiersa Besari : Morphological Study (Journal of Social And Education Research, 2023)
Study This aim For describe function and meaning existing affixes in lyrics song Fiersa enlarge . Method used is descriptive qualitative , Object study This is lyrics songs that have analyzed . Source of data used originate from lyrics song Fiersa enlarge in the place album I go home . Data collection techniques used in study This is observation and documentation . Deep data analysis techniques study This done through stage observation , stage identification , and stage descriptive . Based on results research conducted by researchers , can concluded that exists function and meaning in lyrics song Fiersa Enlarge that there are 84 data in the form function and meaning affixes that consist from prefix , suffix , confix , and simulfix . Result of study This expected No only make as source study related with affix , however expected too beneficial as reference  For do study next related with affixation .